Comparative Analysis of NS5 Protein for Tick Borne Encephalitis Virus Strains in three Virus Subtypes - U. V. Potapova (Acta Biomedica Scientifica, 2019)
Non-structural protein 5 (NS5) of tick-borne encephalitis virus is an enzyme which is responsible for a copying of viral RNA, and it has a strong structural similarity to RNA polymerases of another RNA virus families. The strains of the virus are separated into three subtypes, which differ by specific mutations in virus proteins, including NS5 protein. The methods of structural bioinformatics allow to construct a model of NS5 protein for several strains of the virus.The paper presents the comparative analysis of sequences and structures of NS5 protein, for three subtypes of the tick-borne encephalitis virus. The segments of protein were identified where the highest difference between subtypes and within subtypes is observed. These segments, where most of the mutations are accumulated, are located in methyltransferase domain, in the inter-domain interface, and in the three subdomains of polymerase domain. The association between the locations of mutations in NS5 protein and the flexibility of a protein backbone was observed using normal mode analysis. Namely, the most important mutations are located in the parts of protein where the amplitude of synchronous oscillations estimated using normal mode analysis is the highest: in the second zinc binding pocket within polymerase domain, in the N-terminal extension within inter-domain interface, and around an active site of methyltransferase domain.